The Influence of Entrepreneurial Orientation, Market Orientation, and Product Innovation on the Marketing Performance of the Batik Industry - Swasti Pangestu, Brigitta; Nuvriasari, Audita (Jurnal Inovasi Global, 2024)
This research is motivated by the need to understand the factors that influence the marketing performance of the batik industry in the city of Surakarta, which is one of the leading batik production centers in Indonesia. Batik not only has high cultural value but is also an important industry for the local economy, especially through Micro, Small and Medium Enterprises (MSMEs). This research aims to analyze the influence of entrepreneurial orientation, market orientation, and product innovation on the marketing performance of the batik industry in the city of Surakarta. Quantitative methods were used with the population of batik MSME actors in the city, and a sample of 100 actors was selected through purposive sampling, with the criteria of active operation for a minimum of 3 years according to Sugiyono (2015). Data was collected through a questionnaire whose validity and reliability have been tested. The results of the analysis show that entrepreneurial orientation, market orientation and product innovation play an important role in improving the marketing performance of batik MSMEs in Surakarta City. Increasing and implementing entrepreneurial and market orientation contributes significantly to marketing growth and performance. Intensive product innovation also has a positive impact on marketing performance. Therefore, a strategy that focuses on developing these three aspects is considered key for batik MSME entrepreneurs to achieve sustainable growth and improve their marketing performance. In addition, companies need to strengthen internal factors such as product innovation, service quality and operational excellence to increase efficiency, effectiveness and customer satisfaction. Alignment of marketing strategies with in-depth market analysis and superior customer service is also necessary to strengthen the position in the market.